UF/IFAS Standardized Fertilization Recommendations for Agronomic Crops - Rao Mylavarapu; David Wright; Gerald Kidder (EDIS, 2021)
This publication presents in abbreviated form the fertilization recommendations for agronomic crops based on soil tests performed by the UF/IFAS Extension Soil Testing Laboratory (ESTL). It contains the basic information from which ESTL soil-test reports and fertilization recommendations are generated.